Biologically false positive reactions to serological tests for syphilis - Kostant, George H. (1956)
The frequency of biologically false positive reactions to serological tests for syphilis depends on a number of factors, including the individual immunological response, the number and type of serological tests performed, and the stage of the disease producing such reactions; the relative importance of such factors is discussed. The author also considers in detail the diseases or conditions giving rise to acute or chronic biologically false positive reactions. A variety of verification tests exists for differentiating the true syphilitic reaction from the biologically false positive reaction, but none is so accurate as the Treponema pallidum immobilization and immune adherence tests, which the author considers should be used when others have proved inconclusive. In the final section of his paper, he indicates the steps to be followed in attempting to distinguish between latent syphilis and biologically false positive reactions in persons with positive serological tests but no anamnestic or clinical evidence of syphilis.